Distributions and risk assessment of heavy metals in solid waste in lead-zinc mining areas and across the soil, water body, sediment and agricultural product ecosystem in their surrounding areas - Zhi-qiang Wu; Hai-ying Li; Liu-yan Lü; Guo-jun Liang; Ting-ting Wu; Jiang-xia Zhu (China Geology, 2025)
ABSTRACT: To identify the root causes of heavy metal contamination in soils as well as prevent and control such contamination from its sources, this study explored the accumulation patterns and ecological risks of heavy metals like Cd and Pb in solid waste in mining areas and across the water body, sediment, soil and agricultural product ecosystem surrounding the mining areas. Focusing on the residual solid waste samples in lead-zinc deposits in a certain area of Guizhou Province, along with samples of topsoils, irrigation water, river sediments, and crops from surrounding areas. This study analyzed the distributions of eight heavy metals, i.e., Cd, As, Cr, Hg, Pb, Zn, Cu, and Ni, in the samples through field surveys and sample tests. Furthermore, this study assessed the contamination levels and ecological risks of heavy metals in soils, sediments, and agricultural products using methods such as the single-factor index, Nemerow composite index, and potential ecological risk assessment. The results indicate that heavy metals in the solid waste samples all exhibited concentrations exceeding their risk screening values, with 60% greater than their risk intervention values. The soils and sediments demonstrate slight and moderate comprehensive ecological risks of heavy metals. The single-factor potential ecological risks of heavy metals in both the soil and sediment samples decreased in the order of Hg, Cd, Pb, As, Cu, Zn, Cr, and Ni, suggesting the same sources of heavy metals in the soils and sediments. Most of the agricultural product samples exhibited over-limit concentrations of heavy metals dominated by Cd, Pb, Ni, and Cr, excluding Hg and As. The agricultural product assessment using the Nemerow composite index reveals that 35% of the agricultural product samples reached the heavy metal contamination level, implying that the agricultural products from farmland around the solid waste dumps have been contaminated with heavy metals. The eight heavy metals in the soil, sediment, and agricultural product samples manifested high coefficients of variation (CVs), indicating pronounced spatial variability. This suggests that their concentrations in soils, sediments, and agricultural products are significantly influenced by human mining activities. Additionally, the agricultural products exhibit strong transport and accumulation capacities for Cd, Cu, and Zn.